2014
DOI: 10.1038/ncomms5197
|View full text |Cite
|
Sign up to set email alerts
|

Source identification of the Arctic sea ice proxy IP25

Abstract: Analysis of the organic geochemical biomarker IP 25 in marine sediments is an established method for carrying out palaeo sea ice reconstructions for the Arctic. Such reconstructions cover timescales from decades back to the early Pleistocene, and are critical for understanding past climate conditions on Earth and for informing climate prediction models. Key attributes of IP 25 include its strict association with Arctic sea ice together with its ubiquity and stability in underlying marine sediments; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
152
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 59 publications
17
152
1
Order By: Relevance
“…4b) further highlights the different regimes observed in ice-free and icedominated surface waters. IP25 is a proxy of sea ice based on a highly branched monounsaturated isoprenoid alkene found in some sea ice diatoms which, however, generally account for 5 % of the total sea ice taxa (Belt et al, 2007;Brown et al, 2014). The IP25 concentrations varied by several orders of magnitude over the study area showing low concentrations in the open-water western region while the sea-ice-dominated surface waters to the east exhibited high concentrations especially at station 31b ( Fig.…”
Section: Source Of the Pom (> 10 µM) Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) further highlights the different regimes observed in ice-free and icedominated surface waters. IP25 is a proxy of sea ice based on a highly branched monounsaturated isoprenoid alkene found in some sea ice diatoms which, however, generally account for 5 % of the total sea ice taxa (Belt et al, 2007;Brown et al, 2014). The IP25 concentrations varied by several orders of magnitude over the study area showing low concentrations in the open-water western region while the sea-ice-dominated surface waters to the east exhibited high concentrations especially at station 31b ( Fig.…”
Section: Source Of the Pom (> 10 µM) Fractionmentioning
confidence: 99%
“…Species include Pleurosigma stuxbergii var. rhomboide, Haslea crucigeroides (and/or Haslea spicula) and Haslea kjellmanii (Brown et al, 2014). Briefly, lipids were extracted via sonication using a dichloromethane/methanol solution (2 : 1 v/v × 3).…”
Section: Bulk Carbon Isotopes and Biomarker Analysesmentioning
confidence: 99%
“…1; Belt et al, 2007), a C 25 highly branched isoprenoid (HBI) lipid made uniquely by certain Arctic sea ice-dwelling diatoms (Brown et al, 2014), has been suggested to provide a more direct measure of past sea ice when detected in underlying sediments (see Belt and Müller, 2013 for a recent review). Importantly, IP 25 has been identified in sediments from a large number of surface sediments from seasonally ice-covered Arctic locations and downcore records spanning timescales from recent decades (Müller et al, 2011;Stoynova et al, 2013;Xiao et al, 2013;Navarro-Rodriguez et al, 2013), the Holocene (Vare et al, 2009;Müller et al, 2012) and even longer Knies et al, 2014;Müller and Stein, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1). In recent years, the analysis of the biomarker IP 25 ('Ice Proxy with 25 carbon atoms') 14 , a mono-unsaturated highly branched isoprenoid lipid biosynthesized by certain sea ice diatoms 15 , has become an established proxy method for the reconstruction of Arctic sea ice 16 . The presence (absence) of IP 25 in Arctic marine sediments is especially sensitive to the past occurrence (absence) of sea ice 16 , while abundance variations are usually consistent with corresponding directional changes in sea ice cover 16 .…”
mentioning
confidence: 99%